Experimental and analytical study of temperatures developed by the heat of hydration of high-strength self-compacting mass concrete - Del Savio, Alexandre Almeida (2025)
This study addresses the gap in research on large-scale high-performance concrete (HPC) structures that exhibit self-compacting characteristics and high compressive strength through a detailed case study. It examines the temperature evolution due to hydration heat in a significant HPC structure consisting of an L-shaped reaction slab and wall arrangement. It is heavily reinforced and constructed for a structural laboratory in Lima, Peru. The investigation involved comprehensive instrumentation of the laboratory's reaction slab and wall to assess the impact of boundary conditions on temperature dynamics. Utilizing fifteen thermocouples, temperatures were monitored at various depths, and their progression over time was analyzed. Findings revealed that the peak temperatures reached 78.3°C in the slab and 74.6°C in the wall. Notably, the timing of formwork removal played a critical role in the thermal behavior of the reaction wall, significantly affecting its heating and cooling rates compared to the reaction slab. Despite these variations, the maximum established temperature gradients were not surpassed. Furthermore, the study critically evaluates the ACI method for predicting peak temperatures, identifying an average prediction error of 11.25 % against experimental outcomes. These insights contribute valuable data on the thermal performance of HPC in substantial structural elements, with broader implications for design and construction practices.